Insight into the photophysics of strong dual emission (blue & green) producing graphene quantum dot clusters and their application towards selective and sensitive detection of trace level Fe3+ and Cr6+ ions. Issue 45 (16th July 2020) - Bharathi, Ganapathi; Nataraj, Devaraj; Premkumar, Sellan; Saravanan, Padmanaban; Thangadurai, Daniel T.; Khyzhun, Oleg Yu; Senthilkumar, Kittusamy; Kathiresan, Ramasamy; Kolandaivel, Ponmalai; Gupta, Mukul; Phase, Deodatta
Abstract : Schematic representation for the origin of blue and green emissions, and the resultant PL emission spectra from the GQD interconnected cluster-type sample. Abstract : Graphene-nanostructured systems, such as graphene quantum dots (GQDs), are well known for their interesting light-emitting characteristics and are being applied to a variety of luminescence-based applications. The emission properties of GQDs are complex. Therefore, understanding the science of the photophysics of coupled quantum systems (like quantum clusters) is still challenging. In this regard, we have successfully prepared two different types of GQD clusters, and explored their photophysical properties in detail. By co-relating the structure and photophysics, it was possible to understand the emission behavior of the cluster in detail. This gave new insight into understanding the clustering effect on the emission behaviour. The results clearly indicated that although GQDs are well connected, the local discontinuity in the structure prohibits the dynamics of photoexcited charge carriers going from one domain to another. Therefore, an excitation-sensitive dual emission was possible. Emission yield values of about 18% each were recorded at the blue and green emission wavelengths at a particular excitation energy. This meant that the choice of emission color was decided by the excitation energy. Through systematic analysis, it was found that both intrinsic and extrinsic effects contributed to the blue emission, whereas only the intrinsic effect contributed to the green emission. These excitation-sensitive dual emissive GQD clusters were then used to sense Fe 3+ and Cr 6+ ions in the nanomolar range. While the Cr 6+ ions were able to quench both blue and green emissions, the Fe 3+ ions quenched blue emission only. The insensitivity of the Fe 3+ ions in the quenching of the green emission was also understood through quantum chemical calculations.